Psychological variables as correlates of university maladjustment behaviour (2008)
The goal of the study was to examine the influence of some psychosocial variables like personality factors (extroversion, agreeableness, neuroticism, conscientiousness and openness), gender (male and female) and age in predicting university maladjustment. The participants, (M-42 & F-92) were 134 students in the age range 16-30 years randomly selected from a private University in Nigeria. The Big Five Personality inventory (BFI) and University Maladjustment Scale (UMS) were used to collect data Multiple Regression Analysis, Analysis of Variance (ANOVA) and t-test statistics were used to analyze the data. The result showed that all the psychosocial variables jointly predicted 87% of the University maladjustment variance. The implications in terms of screening fresh intakes into universities and minimizing student unrest were discussed.